HONEY SUPPLEMENTATION IN LACTATE RINGER-EGG YOLK EXTENDER ON QUALITY OF PELUNG CHICKEN SPERMATOZOA POST-CHILLING - Hidayat, Nu'man -; Ismoyowati, Ismoyowati -; Hidayah, Chomsiatun Nurul; Nugroho, Aras Prasetiyo (Jurnal Kedokteran Hewan, 2021)
The purpose of this research was to determine the influence of honey supplementation in lactate ringer-egg yolk extender with 0.025% sodium dodecyl sulfate and 2% vitamin E addition (LREYSE) on the quality of Pelung chicken spermatozoa preserved at 5 C for 72 hours.Semen was collected from three Pelung chickens once per day over a course of three days using the dorsal-abdominal massage method. Semen was divided into 5 treatment groups of honey supplementation that are 0% as control (LREYSEH0), 1% (LREYSEH1), 2% (LREYSEH2), 3% (LREYSEH3), and 4% (LREYSEH4). This liquid semen was observed for sperm motility and viability every 12 hours. Complete random designrepeated measurement with 4 replications was used in this study. The results showed the motility and viability of spermatozoa in LREYSEextender with 2% honey supplementation (61.251.25% and 71.500.74%) was significantly higher (P0.05) than other treatments that are 0% (51.251.25% and 61.881.36%), 1% (52.501.44% and 63.251.38%), 3% (51.251.25% and 61.631.48%), and 4% (50.002.04% and 60.632.29%) of honey supplementation in extender at 36 hours of storage until the end of the observation at 72 hours of incubation. According to the results of this study, it can be concluded that the 2% honey supplementation in extender is the best treatment to maintain sperm motility and viability for 72 hours of storage.